Estimating potential menhaden consumption by double-crested cormorants along the coast of North Carolina - Watts, Bryan D.; Paxton, Barton J.; Hines, Chance; Anderson, Scott K. (Frontiers in Marine Science, 2023)
The south Atlantic coast supports one of the highest assemblages of non-breeding double-crested cormorants (Nannopterum auritum) known and is a convergence area for Atlantic menhaden (Brevoortia tyrannus) during the winter months. We surveyed cormorants along the coast of North Carolina and used a bioenergetics approach to estimate potential menhaden consumption. We estimated cormorant numbers using a network of repeatable aerial transects along the outer coast (366 km) and within sounds (266 km) during fall migration, winter and spring migration (2019-2021). We estimated the number of bird days, metabolic demand and menhaden equivalents of demand. Cormorant numbers peaked around 122,000 to 131,000 during southward migration, reached a low of 30,000 to 39,000 in winter and then increased to 67,000 to 68,000 during northward migration. We did not capture the peak of spring migration during the study period (20 November through 24 March). We estimated the number of cormorant days within the study period to be 8.6 x 106 and 9.2 x 106 for the two field seasons respectively. We estimated that cormorants consumed approximately 5,334 and 5,660 mt of menhaden equivalents within the study area. Estimated consumption peaked between 76 and 81 mt-d during fall passage and reached a low of 19 and 24 mt-d during the winter. Annual menhaden take by humans and predatory fish is around 354,000 mt. Menhaden consumption by cormorants within the study area represents 4% of the commercial and recreational take and 7% of the estimated consumption by predatory fish or 2.5% of the known take.